Enhancement of Calcium Oxide (CaO) for Carbon Dioxide (CO2) Capture - Arpin, Mohamad Taufiq (SENRA Academic Publishers, Burnaby, British Columbia, 2011)
Calcium Oxide (CaO) has a potential to be developed as adsorbent material to capture CO2 at high temperature. This work provides review on the performance of the sorbent in term of source of the material and also the methods of preparation. On the other hand, the experimental research on modification CaO using ethanol-water hydration method was performed. Result on the modified CaO using thanol-water hydration method has show improvement on the capturing performance from 20.16% to 72.65% conversion in thermo gravimetric analyzer (TGA). In addition, the performance of this modified CaO has maintained over 50% conversion after 5 cycles. The X-ray diffraction (XRD) investigation concluded that the CaO was converted to the Ca(OH)2 after modification and its characteristics have improved in which the surface area and pore volume has evolved from 2.18m2/g and 0.006m3/g to 29.22m2/g and 0.157m3/g, respectively. The comparison with other similar work shows different in performance observed and this is due to different CaO source used. In conclusion, ethanol water hydration has proven enhancing CO2 capture erformance and it prolonged the performance of the adsorbent for multi-cycles utilization.